2003
DOI: 10.1029/2002gl016811
|View full text |Cite
|
Sign up to set email alerts
|

The aqueous phase yield of alkyl nitrates from ROO + NO: Implications for photochemical production in seawater

Abstract: [1] Alkyl nitrates have been observed in remote oceanic regions of the troposphere and in the surface ocean. The mechanism for their production in the oceans is not known. A likely source is the reaction of ROO + NO (where R is an alkyl group). Steady-state laboratory experiments show that alkyl nitrates are produced in the aqueous phase via this reaction, with branching ratios of 0.23 ± 0.04, 0.67 ± 0.03, and 0.71 ± 0.04 for methyl, ethyl, and propyl nitrate respectively. The branching ratios in aqueous solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 25 publications
4
59
0
Order By: Relevance
“…This reaction has previously been observed during photochemical experiments with seawater (Dahl et al, 2003;Moore and Blough, 2002). In seawater, NO can be produced from the photolysis of nitrite (Zafiriou and MacFarland, 1981;Zafiriou and True, 1979b).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…This reaction has previously been observed during photochemical experiments with seawater (Dahl et al, 2003;Moore and Blough, 2002). In seawater, NO can be produced from the photolysis of nitrite (Zafiriou and MacFarland, 1981;Zafiriou and True, 1979b).…”
Section: Introductionmentioning
confidence: 94%
“…The ROO and NO radicals can then react to produce alkyl nitrates, with a high yield as shown by Dahl et al (2003). Photochemical incubation studies with seawater in the laboratory have shown alkyl nitrate production at rates sufficient to account for surface ocean concentrations of methyl and ethyl nitrate observed in the Atlantic Ocean (Chuck et al, 2002;Dahl et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations